The Fall of Five: Lorien Legacies #4 - Lore, Pittacus (New York : Harper, 2013)
The Garde is hopelessly outmatched by the annihilating Mogadorian ruler and draws unexpectedly close to finding the last remaining member of their group of alien survivors.
Keywords: Extraterrestrial beings -- Fiction; Extraterrestrial beings -- Fiction; Science fiction